IMPACTS OF COVID-19 PANDEMIC ON CONSUMPTION BEHAVIOR OF COLLEGE STUDENTS IN POLITANI PAYAKUMBUH - Iis Ismawati; Sri Nofianti; Hidayat Raflis; Riva Hendriani (Faculty of Animal and Agricultural Science, Diponegoro University, 2021)
Covid-19 has drastically changed the learning system in almost all universities in Indonesia.Learning online systems lead to increased expenses for buying internet packages and is thought to have an impact on the food and non-food consumption patterns of students. This research evaluates the consumption behavior of the Politani payakumbuh’s Student College in the context of Covid-19 emergence. The data collection technique used was simple random sampling. Data collection was carried out during July-September 2020, using an online questionnaire, distributed via Whatsapp group. Quantitative descriptive data analysis approach to 474 respondents is obtained, who have filled out the questionnaire. Two respondents have been excluded because the data is incomplete. The results of the study stated that the Covid-19 pandemic had an impact on decreasing parental income (85%) and then followed by a reduction in student's monthly allowance (98,5%). The decrease in the monthly student allowance was allegedly due to a decrease in the parents' income. Percentage of students' average monthly allowance at intervals > IDR 500,000 decreased from 42% to 31%. This decrease in student income has an impact on changes in food and non-food consumption patterns. The percentage of food (food, drinks, and snacks) expenditure incline to fall, while non-food expenditure, especially communication costs, rose quite sharply (83%). This research also contributes to supporting the existence of Keynes's classical assumption theory. Practically this study can be used as input for the government in implementing effective learning policies in the New Normal Era.